2011
DOI: 10.7150/ijbs.7.244
|View full text |Cite
|
Sign up to set email alerts
|

Glibenclamide or Metformin Combined with Honey Improves Glycemic Control in Streptozotocin-Induced Diabetic Rats

Abstract: Diabetes mellitus is associated with deterioration of glycemic control and progressive metabolic derangements. This study investigated the effect of honey as an adjunct to glibenclamide or metformin on glycemic control in streptozotocin-induced diabetic rats. Diabetes was induced in rats by streptozotocin. The diabetic rats were randomized into six groups and administered distilled water, honey, glibenclamide, glibenclamide and honey, metformin or metformin and honey. The animals were treated orally once daily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
133
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(154 citation statements)
references
References 52 publications
15
133
4
2
Order By: Relevance
“…In the present study the STZ induced diabetic rats developed symptoms of renal dysfunction, as shown by elevated serum urea, uric acid and creatinine concentrations. Patel et al [66] and Erejuwa et al [67] suggested that DM leads to an elevation in the oxidative damage, considerable injury in the glomeruli, a marked increase in the protein glycosylation, disorders in matrix protein synthesis and increase in treansforming growth factors-beta (TGF-β). Mir et al [68] postulated that the change changes in serum urea and creatinine of STZ diabetic animals could be attributed to the functional and/or morphological changes in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study the STZ induced diabetic rats developed symptoms of renal dysfunction, as shown by elevated serum urea, uric acid and creatinine concentrations. Patel et al [66] and Erejuwa et al [67] suggested that DM leads to an elevation in the oxidative damage, considerable injury in the glomeruli, a marked increase in the protein glycosylation, disorders in matrix protein synthesis and increase in treansforming growth factors-beta (TGF-β). Mir et al [68] postulated that the change changes in serum urea and creatinine of STZ diabetic animals could be attributed to the functional and/or morphological changes in the kidneys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that antioxidants and some hypoglycemic drugs can prevent oxidation of LDL (Fava et al, 2002, Maritim et al, 2003, Rahimi et al, 2005. Besides, evidence indicates that antioxidants can ameliorate lipid abnormalities (Rahimi et al, 2005, Erejuwa et al, 2011d. The beneficial effects of antioxidants on glycemic control (blood glucose, fructosamine and glycosylated hemoglobin) in diabetes have also been documented (Rahimi et al, 2005, Lai, 2008, Erejuwa et al, 2010a2011d).…”
Section: Other Potential Beneficial Effects Of Hypoglycemic Drugs (Anmentioning
confidence: 99%
“…Similar report were shown by Erejuwa, et al in diabetic rat model. 28 Pancreatic Lipase was assessed to detect pancreatic function and increased Lipase level in D-ISP (40.13+5.82) as compared to NC, showed damage to pancreatic tissue as compared to NC. SGPT is a hepatic enzyme and biomarker for abnormal liver function.…”
Section: Discussionmentioning
confidence: 99%